Successful Management of a Stab Wound to the Left Ventricle - Gillani, Jaleed Ahmad; Khan, Hamza AR; Irfan, Omar; Fatimi, Saulat H (Cardiovascular Journal, 2016)
A 24 year old male presented to the emergency room with a 2 hour history of knife stab wound. He was haemodynamically stable with good bilateral air entry. However on X-ray an enlarged cardiac silhouette was seen. The patient suddenly became hypotensive and on suspicion of cardiac tamponade a catheter was introduced in pericardial space, but the measure was unsuccessful and he was rushed to the Operating Room. During the surgery a 2 cm long laceration was identified in the mid-left ventricular (LV) wall less than 1mm away from the Left Anterior Descending (LAD) Artery. The Left Anterior Descending Vein was damaged which was then repaired along with the ventricular wall by the interrupted pledgeted 3-0 prolene suture, whilst a cardiopulmonary bypass was kept on the stand by. The patient was checked for a ventricular septal defect via an intraoperative echocardiography. Subsequently, he had an uneventful recovery and was discharged. Cardiovasc. j. 2016; 9(1): 60-63